WOOLWICH MASSAGE AND LAVENDER AROMATHERAPY AS COMPLEMENTARY CARE FOR POSTPARTUM LACTATION - Santi Wahyuni; Anifa Ferhika Cahya (Journal of Maternity Care and Reproductive Health, 2026)
This study aims to describe the implementation of Woolwich Massage and lavender aromatherapy as complementary care to support postpartum lactation, and to explore mothers’ physiological and psychological responses to the intervention. The research design used a qualitative descriptive case study of two postpartum mothers in the working area of UPTD Dukupuntang Health Center, Cirebon Regency. The intervention was given for five consecutive days, twice daily, with a 15-minute session. Data collection was carried out through in-depth interviews, observations, and physical examinations. The study found increased breast milk production, increased breastfeeding frequency, and improved indicators of breastfeeding adequacy in both clients. In addition to physiological changes, this intervention also improves psychological well-being, characterized by decreased anxiety, increased relaxation, and greater maternal confidence in breastfeeding. The difference in response between clients was influenced by the initial psychological state, previous breastfeeding experience, and readiness to receive intervention. These findings suggest that Woolwich Massage and lavender aromatherapy can be used as non-pharmacological complementary care to support postpartum lactation and may be integrated into maternity nursing practice as a holistic, relaxation-based approach.